Village Fund Accountability: Does Village Chief’s Leadership Matter More Than Staff Competence? - Muhammad Taufiq (Trescode Green Organization, 2024)
This study aims to investigate and compare the influence of leadership and competence on village fund accountability. While both factors are theoretically essential for sound financial governance, empirical evidence has shown inconsistent results regarding which variable acts as the primary driver for accountability. This research addresses the debate by evaluating whether the